log(x)+log(x-5)=log(5x)

Simple and best practice solution for log(x)+log(x-5)=log(5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(x)+log(x-5)=log(5x) equation:


Simplifying
log(x) + log(x + -5) = log(5x)

Multiply glo * x
glox + log(x + -5) = log(5x)

Reorder the terms:
glox + glo(-5 + x) = log(5x)
glox + (-5 * glo + x * glo) = log(5x)
glox + (-5glo + glox) = log(5x)

Reorder the terms:
-5glo + glox + glox = log(5x)

Combine like terms: glox + glox = 2glox
-5glo + 2glox = log(5x)

Remove parenthesis around (5x)
-5glo + 2glox = glo * 5x

Reorder the terms for easier multiplication:
-5glo + 2glox = 5glo * x

Multiply glo * x
-5glo + 2glox = 5glox

Solving
-5glo + 2glox = 5glox

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-5glox' to each side of the equation.
-5glo + 2glox + -5glox = 5glox + -5glox

Combine like terms: 2glox + -5glox = -3glox
-5glo + -3glox = 5glox + -5glox

Combine like terms: 5glox + -5glox = 0
-5glo + -3glox = 0

Factor out the Greatest Common Factor (GCF), '-1glo'.
-1glo(5 + 3x) = 0

Ignore the factor -1.

Subproblem 1

Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(5 + 3x)' equal to zero and attempt to solve: Simplifying 5 + 3x = 0 Solving 5 + 3x = 0 Move all terms containing g to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 0 + -5 3x = 0 + -5 Combine like terms: 0 + -5 = -5 3x = -5 Add '-3x' to each side of the equation. 3x + -3x = -5 + -3x Combine like terms: 3x + -3x = 0 0 = -5 + -3x Simplifying 0 = -5 + -3x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -4(j+2)=5(j-3) | | c+(3c)+(2.5c)=60 | | (7-x)(x^2+20)= | | (x-3)=50 | | 8+2.50x=30 | | 6x+6=-8+2x+22 | | 0.23(10000)-0.04y=0.06(y+10000) | | 12-4m=36-12m | | x^3-200x^2+2x=0 | | 8k+5=2k-15 | | 3-2x^2=7 | | -4(-x-3)= | | 7+57=q | | 2(5x+3)+11x= | | 7+57= | | 8+10x=-11x | | (7x+4)=(18x-6) | | 2(l+0.2l)=240 | | 2(18)=p | | dx=(x^2-1)*dy | | 16x=25y | | 0.16(y-9)+0.02y=0.06y-0.9 | | 16x+25y=0 | | 7w-2w= | | -3(6p+5)-2(5-17p)=3(9+5p) | | x^2-17=81 | | 5/6-x/18=1/9 | | 7b=3-2b | | 4.71=3.14a(2) | | (-5x)+3x= | | 43+34= | | 2w=40 |

Equations solver categories